2018
DOI: 10.1038/s41565-018-0252-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrical tuning of elastic wave propagation in nanomechanical lattices at MHz frequencies

Abstract: Nanoelectromechanical systems (NEMS) that operate in the megahertz (MHz) regime allow energy transducibility between different physical domains. For example, they convert optical or electrical signals into mechanical motions and vice versa. This coupling of different physical quantities leads to frequency-tunable NEMS resonators via electromechanical non-linearities. NEMS platforms with single- or low-degrees of freedom have been employed to demonstrate quantum-like effects, such as mode cooling, mechanically … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 31 publications
1
92
0
Order By: Relevance
“…The ability to tune the response of such materials also remains limited, which is a roadblock for interacting with different devices and phenomena, for device multifunctionality, and for spatially tailoring the materials' effective properties for strategies such as transformation acoustics or topological design . Prior lattices and acoustic metamaterials operating in the MHz–GHz regime have experimentally demonstrated tuning of <20% to ≈90% of the bandgap center and stop band cutoff frequencies, respectively, and prior self‐assembled phononic crystals have demonstrated postassembly tuning of <20% of the bandgap center frequency. No prior studies have demonstrated the ability to tune a self‐assembled ultrasonic metamaterial in a spatially localized manner after fabrication of the crystal, which is particularly critical due to the sensitivity of most self‐assembly processes to the properties of the particles and the substrate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to tune the response of such materials also remains limited, which is a roadblock for interacting with different devices and phenomena, for device multifunctionality, and for spatially tailoring the materials' effective properties for strategies such as transformation acoustics or topological design . Prior lattices and acoustic metamaterials operating in the MHz–GHz regime have experimentally demonstrated tuning of <20% to ≈90% of the bandgap center and stop band cutoff frequencies, respectively, and prior self‐assembled phononic crystals have demonstrated postassembly tuning of <20% of the bandgap center frequency. No prior studies have demonstrated the ability to tune a self‐assembled ultrasonic metamaterial in a spatially localized manner after fabrication of the crystal, which is particularly critical due to the sensitivity of most self‐assembly processes to the properties of the particles and the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The tunability, which we note is nonreversible (in contrast to refs. ), is achieved through the use of optical‐microlensing to tailor nanocontact features. Our self‐assembled metamaterials mitigate the aforementioned manufacturing scalability challenges, and have been previously demonstrated in the context of, for instance, surface acoustic wave (SAW) filters to have massive attenuations of −0.25 dB µm −1 (similar to recent phononic crystal filters with −0.31 dB µm −1 attenuation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, by assembling coupled resonators into long-range periodic structures, we can create phononic crystal structures and consequential phononic bands similar to the atomic lattices in crystalline solids and photonic crystal lattices, and their associated band structures. Such devices not only enable fundamental exploration of lattice-based solid-state phenomena including dispersive relation, energy transport, nonlinear dynamics, and topological states in the phononic domain, but also facilitate device functionalities, such as on-chip routing and filtering of radio-frequency (RF) acoustic waves [35,36]. The basic concept in Figure 1 is enabled and reinforced by the agile, additive features in device nanofabrication in the h-BN platform, evading conventional lithographic patterning and its associated chemical resist and contamination.…”
mentioning
confidence: 99%
“…The combination of high-spatial-resolution optical drive and read-out enables full multimodal control of suspended 2D nanomechanical resonators for future NEMS applications. Our highresolution, all-optical approach could be combined with optical beam shaping and spatial light modulation to selectively address an arbitrary subset of resonators within large arrays, a feat not easily achievable with electrostatic gating, or could serve as a point source of propagating mechanical waves for use in 2D nanomechanical circuits 32 and waveguides 33 .…”
mentioning
confidence: 99%